Izobraževanje Elektronski viri v knjižnicah - Kotar, Mojca (Knjižnica, 2007)
The course Electronic resources in libraries carried out by the Bibliotheque nationale de France and Bibliotheque publique d'information within the scope of the programme Courants du monde in November 2006 is presented in the article. The course programme was composed in such a way as to enable the participants to become familiar with all the aspects of selection, digitization, use and preservation of electronic resources in libraries. It was conducted in the form of lectures, the most interesting of which are presented in the article, and visits connected with the lecture topics. The participants were systematically familiarized with electronic resources and were able to compare the circumstances prevailing at their home institutions among themselves.
Keywords: digitalne knjižnice; digitization; digitalizacija; elektronski viri; education; izobraževanje; France; Francija